Estimating discharge from the Godavari River using ENVISAT, Jason-2, and SARAL/AltiKa radar altimeters. Issue 4 (2nd April 2016) - Sridevi, T.; Sharma, Rashmi; Mehra, P.; Prasad, K. V. S. R.
ABSTRACT: The present work discusses the application of radar altimeters on-board Environmental Satellite (ENVISAT), Jason-2, and Satellite with Argos and AltiKa (SARAL) missions to estimate the Godavari River discharge draining into the Bay of Bengal for the period 2002–2014. Ranges retrieved from the ICE-1 and ICE-3 retracker algorithms were used to estimate the river heights, followed by important range corrections. In situ radar gauge data at Yanam station and river discharge data from Dowlaiswaram dam were used to construct rating curves. This technique was applied to the ENVISAT (2002–2010), SARAL (2013–2014) derived river heights at Yanam and ENVISAT (2002–2010), SARAL (2013–2014), Jason-2 (2008–2014) derived river heights at Bhadrachalam. A hydrodynamic model was used to validate the ENVISAT and SARAL derived heights at Yanam; found that the modelled data are highly correlated with correlation coefficient r = 0.9. We estimate the standard errors of river height for all three altimeters. The values range from 0.15 to 0.40 m, quite within the acceptable accuracy of altimetry for hydrology/river applications. The root mean square error (RMSE) between ENVISAT and in situ discharge is 366 and 253 m 3 s −1 at Yanam and Bhadrachalam, respectively. With Jason-2, it is around 620 m 3 s −1 at Bhadrachalam. The residual error in individual altimetry data estimates is of the order ±15–25% of the in situ river discharge. The standard errors from ENVISAT at Yanam (Bhadrachalam) for the years 2007, 2008, 2009, and 2010 are 0.10% (14.70%), 10.30% (2.80%), 8.20% (26.50%), and 25.30% (10.20%), respectively; which are within the range of acceptable errors for discharge measurements (10–25%).